THE OCCUPYING POWER ACCORDING TO THE INTERNATIONAL HUMANITARIAN LAW: CASE STUDY IN GAZA STRIP - Mohamad Afdha Lardo (International Law Department, Faculty of Law Universitas Padjadjaran, 2020)
Abstract Conflict in Gaza Strip involving Israel and Palestine has continuously attracted international concerns. Under the strict authority of Israel, humanitarian issues materialize in the strip as Gaza’s inhabitants undergo crises including energy and subsistence while Israel fails to fulfill the basic needs of the people. In 2007, Jaber Al-Bassiouni Ahmed with his associates sought legal remedy to the Supreme Court of Israel to clarify their rights inhabiting the Gaza Strip. The purpose of this article is to explain whether international humanitarian law could be implemented to the occupying power of Israel in Gaza Strip and elucidate the limitation of the occupying power regarded by the law. Achieving this explanation requires a qualitative legal approach. It emphasizes on documents scrutiny using the perspectives of primary, secondary, and tertiary laws. The research result shows that under the regime of international humanitarian law, “alien occupation” is the key to regulate the Gaza Strip against the regime of the occupying power by Israel. The one-year rule in the Case of Gaza Strip indicates that Israel held the occupying power of the territory as not only did Israel act as a controller but also it participated in the physical activities to regulate the lives of Gaza residents in addition to the limitation of the functions of Palestinian Authority posed by Israel. Keywords: Gaza Strip, International Humanitarian Law, Occupying Power Abstrak Konflik di Jalur Gaza yang melibatkan Israel dan Palestina terus menarik perhatian internasional. Di bawah kekuasaan Israel, isu humaniter mencuat di jalur tersebut karena penduduk Gaza mengalami krisis energi dan mata pencaharian, sementara Israel tidak memenuhi kebutuhan dasar hidup penduduk tersebut. Pada tahun 2007, Jaber Al-Bassiouni Ahmed bersama rekan-rekannya mengajukan tinjauan hukum kepada Pengadilan Tinggi Israel untuk mengklarifikasi hak-hak mereka sebagai penduduk di Jalur Gaza. Tujuan penelitian ini adalah untuk menjelaskan apakah hukum humaniter internasional dapat diterapkan dalam kasus penguasa pendudukan di Jalur Gaza oleh Israel dan menjelaskan batasan kekuasaan pendudukan tersebut. Pendekatan kualitatif hukum berbasis studi dokumen dengan perspektif hukum primer, sekunder dan tersier digunakan dalam penelitian ini. Hasil penelitian ini membuktikan bahwa di bawah hukum humaniter internasional, “pendudukan asing” menjadi kunci regulasi yang dapat diterapkan di Jalur Gaza di bawah resim penguasa pendudukan yakni Israel. Aturan “Satu Tahun” di jalur tersebut menunjukan bahwa Israel memegang kendali wilayah tersebut karena Israel tidak hanya bertindak sebagai pengontrol melainkan juga melakukan kegiatan fisik untuk mengatur kehidupan masyarakat Gaza juga membatasi fungsi-fungsi autoritas Palestina. Kata Kunci: Hukum Humaniter Internasional, Jalur Gaza, Penguasa Pendudukan